2014
DOI: 10.2323/jgam.60.7
|View full text |Cite
|
Sign up to set email alerts
|

The early diverging ascomycetous budding yeast Saitoella complicata has three histone deacetylases belonging to the Clr6, Hos2, and Rpd3 lineages

Abstract: We sequenced the genomic DNA and the transcribed RNA of the ascomycetous budding yeast Saitoella complicata, which belongs to the earliest lineage (Taphrinomycotina) of ascomycetes. We found 3 protein-coding regions similar to Clr6 of Schizosaccharomyces (a member of Taphrinomycotina). Clr6 has a structure similar to that of Rpd3 and Hos2 of Saccharomyces. These proteins belong to the class 1 histone deacetylase (HDAC) family. The phylogenetic tree showed that the Clr6, Hos2, and Rpd3 lineages are separated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
0
4
0
3
Order By: Relevance
“…Therefore, documenting that Pneumocystis stimulation of Muc5b via the STAT6/FoxA2 pathway, occurs by inhibition of the FoxA2 repressor and, can be partly reverted by Kaempferol. Other potential pharmacological intervention that has been suggested to modulate the mucus hypersecretion associated to Pneumocystis in infants and patients with COPD, is to increase methylation of histone 3 which is known to suppress STAT6 35 suggesting epigenetic modifications also deserve exploration 35,36 . Modulation of mucus is complex and additional mucogenic pathways like EGFR and NFkB may be involved.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, documenting that Pneumocystis stimulation of Muc5b via the STAT6/FoxA2 pathway, occurs by inhibition of the FoxA2 repressor and, can be partly reverted by Kaempferol. Other potential pharmacological intervention that has been suggested to modulate the mucus hypersecretion associated to Pneumocystis in infants and patients with COPD, is to increase methylation of histone 3 which is known to suppress STAT6 35 suggesting epigenetic modifications also deserve exploration 35,36 . Modulation of mucus is complex and additional mucogenic pathways like EGFR and NFkB may be involved.…”
Section: Discussionmentioning
confidence: 99%
“…It also appears that there are two paralogous genes encoding homologs of the Clr6 HDAC (designated CLR61 and CLR62 ), corroborating the phylogenetic study of Nishida, et al . 52 . Our phenotypic studies of the respective paralog mutant strains suggest that these two genes have undergone some degree of neofunctionalization.…”
Section: Discussionmentioning
confidence: 99%
“…We previously attempted to assemble the genome sequence of S. complicata using 454 (Roche) sequences ( 5 ) and Illumina paired-end read pairs ( 6 ). Although these previous assemblies were of a large number of small contigs, at 7,981 contigs (13.0 Mbp) ( 5 ) and 1,800 contigs (14.2 Mbp) ( 6 ), respectively, we found that the amino acid sequences of protein-coding genes identified on the contigs showed the highest similarity to proteins of Pezizomycotina ( 5 , 6 ).…”
Section: Genome Announcementmentioning
confidence: 99%